Analysis of the Escherichia coli extracellular vesicle proteome identifies markers of purity and culture conditions. Issue 1 (1st December 2019) - Hong, Jiwon; Dauros-Singorenko, Priscila; Whitcombe, Alana; Payne, Leo; Blenkiron, Cherie; Phillips, Anthony; Swift, Simon
ABSTRACT: Bacteria release nano-sized extracellular vesicles (EVs) into the extracellular milieu. Bacterial EVs contain molecular cargo originating from the parent bacterium and have important roles in bacterial survival and pathogenesis. Using 8-plex iTRAQ approaches, we profiled the EV proteome of two Escherichia coli strains, uropathogenic (UPEC) 536 and probiotic Nissle 1917. For these strains, we compared the proteome of crude input EVs prepared by ultracentrifugation alone with EVs purified by either density gradient centrifugation (DGC) or size exclusion chromatography (SEC). We further compared the proteome of EVs from bacterial cultures that were grown in iron-restricted (R) and iron-supplemented (RF) conditions. Overall, outer membrane components were highly enriched, and bacterial inner membrane components were significantly depleted in both UPEC and Nissle EVs, in keeping with an outer membrane origin. In addition, we found enrichment of ribosome-related Gene Ontology terms in UPEC EVs and proteins involved in glycolytic processes and ligase activity in Nissle EVs. We have identified that three proteins (RbsB of UPEC in R; YoeA of UPEC in RF; BamA of Nissle in R) were consistently enriched in the DGC- and SEC-purified EV samples in comparison to their crude input EV, whereas conversely the 60 kDa chaperonin GroEL was enriched in the crude input EVs for both UPEC and Nissle in R condition. Such proteins may have utility as technical markers for assessing the purity of E. coli EV preparations. Several proteins were changed in their abundance depending on the iron availability in the media. Data are available via ProteomeXchange with identifier PXD011345. In summary, we have undertaken a comprehensive characterization of the protein content of E. coli EVs and found evidence of specific EV cargos for physiological activity and conserved protein cargo that may find utility as markers in the future. Abbreviation: DGC: density gradient centrifugation; DTT: 1, 4-dithiothreitol; EV: extracellular vesicles; FDR: false discovery rate; GO: Gene Ontology; R: iron-restricted; RF: iron-supplemented; iTRAQ: isobaric tags for relative and absolute quantitation; OMV: outer membrane vesicle; SWATH-MS: sequential window acquisition of all theoretical mass spectra; SEC: size exclusion chromatography.